Relationship between tooth brushing skills and PHP plaque index score of SDN ciburial 01 children: An observational study - Himawati, Marlin; Ardan, Rachman; Randi, Randi (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2024)
ABSTRACT Introduction: Indonesian children are considered to pay less attention to oral health. Various oral problems that are often found in the community are caries and periodontal disease. This is due to not maintaining oral hygiene. Many studies state that proper brushing will affect the status of oral hygiene including the plaque index to be good. purpose of this research is to analyze relationship between tooth brushing skills and the plaque index score of Ciburial 01 Elementary School children. Methods: This research method is observational research with a cross-sectional approach. The cause variable in this study is tooth brushing skills and the effect variable is the plaque index score of SDN Ciburial 01 children occurring simultaneously at one time. The population in this study were students of SDN Ciburial 01 consisting of grades 4, 5 and 6. The minimum sample size from the calculation of the sample size formula for the correlation test was 50 people at SDN Ciburial 01 students. Results: The results of this study show that the Pearson correlation test shows a p-value (0.0001), meaning that there is a significant relationship between tooth brushing skills and plaque index scores. Based on the assessment of the correlation coefficient (r = 0.811), it means that the better the brushing skills, the lower the plaque index score with the strength of the relationship, which is very strong. Conclusion: The conclusion obtained is that there is a relationship between tooth brushing skills and the plaque index score of SDN Ciburial 01 children with an inverse relationship direction, which means that the better the tooth brushing skills, the lower the plaque index score with a level of relationship strength that is very strong.KEY WORDS: Toothbrushing skills, plaque index score, caries Hubungan antara keterampilan menyikat gigi dengan skor indeks plak PHP anak SDN Ciburial 01: studi observasionalABSTRAKPendahuluan: Anak-anak Indonesia dianggap kurang memperhatikan kesehatan gigi dan mulut. Berbagai masalah gigi dan mulut yang sering ditemui di masyarakat adalah karies dan penyakit periodontal. Hal ini disebabkan tidak terjaganya kebersihan gigi dan mulut. Banyak penelitian yang menyatakan bahwa menyikat gigi dengan tepat akan memengaruhi status kebersihan gigi dan mulut termasuk indeks plak menjadi baik. Tujuan penelitian menganalisis hubungan antara keterampilan menyikat gigi dengan skor indeks plak anak SDN Ciburial 01. Metode: Metode penelitian ini adalah penelitian observasional dengan pendekatan cross-sectional. Variabel bebas dalam penelitian ini yaitu keterampilan menyikat gigi dan variabel terikat yaitu skor indeks plak anak SDN Ciburial 01 terjadinya bersamaan dalam satu waktu. Populasi dalam penelitian ini adalah siswa SDN Ciburial 01 terdiri dari kelas 4, 5 dan 6. Jumlah sampel minimal dari hasil perhitungan rumus besar sampel untuk uji korelasi adalah 50 orang pada siswa SDN Ciburial 01. Hasil: Uji korelasi Pearson menunjukkan nilai p-value (0,0001) berarti terdapat hubungan yang signifikan antara keterampilan menyikat gigi dengan skor indeks plak. Berdasarkan penilaian koefisien korelasi (r=-0,811) artinya semakin baik keterampilan menyikat gigi maka semakin rendah skor indeks plaknya dengan tingkat kekuatan hubungan yaitu sangat kuat. Simpulan: Kesimpulan yang didapat yaitu terdapat hubungan antara keterampilan menyikat gigi dengan skor indeks plak anak SDN Ciburial 01 dengan arah hubungan terbalik, yang artinya semakin baik keterampilan menyikat gigi maka semakin rendah skor indeks plaknya dengan tingkat kekuatan hubungan yang sangat kuat.KATA KUNCI: Keterampilan menyikat gigi, skor indeks plak, karies